The impact of mindfulness intervention on negative emotions and quality of life in malignant tumor patients: a systematic review and meta-analysis - Li, Zhang; Lei, Dong; Ting, Li; Yao, Ran; Jing, Wu; Na, Mi (Frontiers in Psychology, 2024)
Objective: This study aims to assess the effect of mindfulness intervention on negative emotions (anxiety and depression) and quality of life in malignant tumor patients. Methods: The databases, including CNKI, VIP, Wanfang, Chinese Biomedical Literature Database disc (CBMdisc), PubMed, Embase, Cochrane Library, and Web of Science (WoS), were searched from inception to January 2024. Randomized controlled trials examining the effects of mindfulness intervention on negative emotions and quality of life in malignant tumor patients were selected. Meta-analysis was conducted using RevMan 5.1. Results: A total of 11 studies involving 993 patients were included. Compared with usual care, mindfulness intervention effectively reduced anxiety [SMD=-0.81, 95% CI (-1.01,-0.60), P<0.00001], depression [SMD=-0.86, 95% CI (-1.01,-0.70), P<0.00001], and improved patients' quality of life [SMD=0.64, 95% CI (0.50,0.78), P<0.00001]. Conclusion: Mindfulness intervention can effectively alleviate negative emotions such as anxiety and depression in malignant tumor patients and positively impact their quality of life.